Effects of Dual and Triple Drug Therapy in Chronic Obstructive Pulmonary Disease Management: An Overview - V, Mizaj Jasira; E, Jereena. (Indian Journal of Pharmacy Practice)
Background: A common and serious disease known as chronic obstructive pulmonary disease is currently the fourth leading cause of death worldwide. Studies have shown that inhaled triple therapy is superior to dual therapy, but side effects include pneumonia and cardiovascular events. The use of triple inhalation therapy has advanced the treatment of chronic obstructive pulmonary disease. The efficacy of inhaled corticosteroids in treating Chronic obstructive pulmonary disease exacerbations increases with higher blood eosinophil levels, has no effect in people with low blood eosinophil levels, and eosinopenia increases the risk of pneumonia. Patients with chronic obstructive pulmonary disease are at high risk of infection, and triple therapy, including inhaled corticosteroids, is not an option for patients with active tuberculosis. Studies have also shown the value of dual therapy for mild exacerbations, particularly in patients who cannot receive inhaled corticosteroid treatment. There doesn’t seem to be a single article that covers all the basics of dual and triple therapy, including the different types of combinations and side effects. Main parts of the summary: GOLD recommends a personalized strategy for treatment initiation based on symptom severity and likelihood of exacerbation. The treatment course may be increased or decreased depending on the presence or absence of key symptoms such as shortness of breath or decreased performance, and the persistence of exacerbations during maintenance therapy. To achieve the best treatment and health outcomes, people with COPD need to understand the nature of their disease, the risk factors for progression, and the roles that patients and healthcare providers should play. People with COPD need to understand the nature of their disease, the risk factors for its progression, and the role they and their health care professionals must play in achieving the best management and health outcomes. The use of triple therapy was found to be associated with an increased risk of pneumonia compared to LABA/LAMA. This suggests that the use of triple therapy may have a higher risk of developing pneumonia compared to the use of LABA/LAMA. However, there were no significant differences between the triple therapy and the two-drug inhaler regarding other adverse events. Conclusion: The risk of pneumonia may be higher with his triple combination therapy, but in terms of other adverse events (e.g. side effects and complications) there is no statistical difference between the two treatment options. However, there was no significant difference. However, severe COPD exacerbations were treated with triple therapy. Additionally it helped to improve lung function and reduce exacerbations. In case of moderate exacerbation, dual treatment was given. Dual Therapy may help to reduce the negative effects of ICS.
Keywords: Dual therapy; Triple therapy; COPD; Inhaled corticosteroids; LABA; LAMA